In situ sensing of salinity in oriented lipid multilayers by surface X-ray scattering - Amenitsch, Heinz (Langmuir : the ACS journal of surfaces and colloids, 2004)
The influence of LiCl solutions on liposomal and surface-supported phosphatidylcholine/water systems (dipalmitoylphosphatidylcholine (DPPC) and 1-palmitoyl-2-oleoylphosphatidylcholine (POPC), respectively) has been studied by small-angle X-ray techniques. In liposomal dispersions of DPPC, an osmotically stressed liquid-crystalline phase, denoted as Lalpha osm, forms readily after rapid mixing with salt solutions. The transition from Lalpha -->Lalpha osm proceeds in two steps. The first step takes place within seconds and is due to water diffusion from the liposome into the bulk solution. The second, slower process (minutes) can be attributed to the relaxation of initially deformed intermediate liposomes into spherical ones. In experiments with aligned lipid bilayers supported on silicon wafers, it was possible to reproducibly exchange different concentrations of LiCl solutions on a single sample and to determine the lattice changes by time-resolved X-ray scattering at grazing incidence. Independently of the deposition technique (spray- or spin-coating, respectively), none of the investigated POPC samples displayed an osmotically stressed liquid-crystalline phase. While liposomes can be considered nearly defect-free, supported bilayer stacks show a high abundance of defects, such as oily streaks typical of the Lalpha phase. Thus, the alkali ions are free to diffuse into the interbilayer water regions and to cause a slight increase of the bilayer separation (about 1 Angstroms). It is concluded that low to medium concentrations of Li+ ions partially screen the attractive van der Waals force between adjacent membrane layers. However, upon annealing the defect regions or regions of high curvature in the oriented lipid matrix, e.g. by low amounts of oleyl alcohol (OA), the system is able to sense osmotic stress upon addition of a salt solution